The analysis of method for diagnosing faults of three-phase asynchronous motor - K. V. Khatsevskiy; A. D. Umurzakova; N. A. Voronina; Yu. B. Icheva (Омский научный вестник)
The article deals with issues related to improving the reliability of electrical equipment in industrial enterprises by implementing fault diagnosis systems. A hardware-software complex for diagnosing faults of a three-phase asynchronous motor is proposed.